Trabalho, migração e comércio ambulante no oeste paranaense: a experiência dos redeiros em Cascavel - PR - Silva, Emeson Tavares (2017)
This research investigates, in the set of the Northeastern workers' practices here, set up in redeiros that sought the west region of Paraná, more particularly the city of Cascavel, from 1998, that make the so-called itinerant commerce in the city, the senses and conditions of Understanding the actions of these subjects in the transformation of the region, as well as the conflicts and estrangements experienced with other local groups for the conquest of space and the right of belonging to the place, thus raising the agenda of expectations and values of these subjects in the dynamics of Their experiences, evidencing relations of identifications and dissidents, established in their conduct. When considering leaving one place and evaluating the change for another, the question that arises lies in the understanding of what is expected and expected of the dwelling, affective bonds, possibilities of food and clothing, activities and labor relations, Of the hours and situations of leisure, of the relations preserved or intentionally interrupted; Finally, of the power relations present in the alternatives sent from the class condition of these workers. In this direction, attention is given to the planned character of these trajectories, to the tensions and the various estrangements, remembered and reworked by the subjects. In the same way, it ventures to give visibility to the networks of these itinerant itineraries, often inconclusive, that permeate the formation of the social landscape of this region.